The Decision of Women in Makassar City to Be Entrepreneurs - Hasniati Hasniati; Dewi Pratiwi Indriasari; Arief Sirajuddin; Abdul Karim (Bina Nusantara University, 2023)
The participation rate of Indonesian women as entrepreneurs is the highest in Southeast Asia. The research aimed to determine the effect of personality factors, socio-cultural factors, and contextual element on the decision-making of female entrepreneurs in Makassar City. The research applied a quantitative-qualitative approach (mixed methods). The total population was 8.756 people. However, after the probability sampling was carried out, the sample of respondents was 382 people. Then, the three informants were determined by purposive sampling to become key informants based on the criteria. The analysis tool used in the test was structural equation model analysis with the help of the AMOS program. The results of the quantitative research and transcripts of the interview process are carried out at the qualitative stage which is analyzed descriptively. The results show that personality factors has a significant effect on the characteristics of female entrepreneurs in Makassar City. Through moderating variables, the results show that contextual elements have significant effect on entrepreneurial decisions. The characteristics of female entrepreneurs are to describe achievement motivation, future orientation, leadership, responsiveness, and creativity for all women in Indonesia to support economic transformation. The decision of women to become entrepreneurs also contributes to the sustainability of the household economy.